Slurry infiltrated fiber concrete properties: a review - Esraa Kh. Abuzaid,; S.A. Osman,; Azrul A Mutalib,; Salah R. Al Zaidee, (Penerbit Universiti Kebangsaan Malaysia, 2024)
“Slurry infiltrated fibrous concrete” refers to a contemporary, high performing fiber-reinforced concrete and infiltrated with a specially designed fiber bed, cement-based slurry. The material has excellent mechanical properties along with high durability and ductility. The SIFCON Laboratory’s research revealed SIFCON to be a unique building material with improved abilities to absorb energy and resist impact, as well as greater ductility and strength. With all these qualities, SIFCON can repair and fortify both reinforced and unreinforced concrete structures. Ductility is currently one of concrete’s most critical characteristics. The issue of brittleness with concrete has been solved by utilizing a high volume of fibers instead of coarse aggregate, which provides stress-resistant properties and increases the ductility of the structural component. However, due to the placement and mixing challenges because of the high volume of fibers’ interlocking action, there is a necessity to design unique production techniques. Since SIFCON compounds are a novel trend in the fields of areas of civil engineering that have a catalytic effect, it is necessary to highlight the few studies that included it so this review paper discusses and presents the behavior of SIFCON under various external loads. The focus is on the effects of the SIFCON mortar type—which substitutes silica fume and/or fly ash for cement—and fiber type—which uses hooked end fiber and micro steel fiber—are the main topic of discussion. The mechanical characteristics and optimal percentages are also reviewed. All previous studies are noted and summaries are made in comprehensive tables, which display the studied parameters and SIFCON mortar mix ratios. In addition to indicating research gaps, for example, future work in this field needs to focus on developing a detailed analytical model that requires the ability to calculate these factors. A better understanding of the SIFCON’s features can serve as a theoretical foundation for future research projects and engineering applications for creating concrete materials for the construction industry.